2017
DOI: 10.18203/2394-6040.ijcmph20172162
|View full text |Cite
|
Sign up to set email alerts
|

Study of workplace violence, its risk factors and perceptions about workplace security in doctors of Paithan

Abstract: Background: Of all work settings, hospitals carry the greatest risk of verbal abuse and threats, with 73% of staff on medical premises suffering abuse. The scenario in Indian subcontinent is also not so bright. Doctors are frequently assaulted in India as well where doctors are shot, even stabbed. Thus this study was undertaken to know the exact prevalence of such incidences in Paithan taluka of Aurangabad district. Methods: A community based cross-sectional study was done in the Paithan taluka of Aurangabad d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…Thus this study reflects the results for the GOVT teaching hospitals only. We found the overall prevalence of WPV in the last 12 months to be 73%.This finding was exactly the same with the finding of PUND SB et al 7 This finding was slightly higher with the findings of Hobbs F.D.R. 4 who found the prevalence to be 63%.…”
Section: Discussionsupporting
confidence: 91%
“…Thus this study reflects the results for the GOVT teaching hospitals only. We found the overall prevalence of WPV in the last 12 months to be 73%.This finding was exactly the same with the finding of PUND SB et al 7 This finding was slightly higher with the findings of Hobbs F.D.R. 4 who found the prevalence to be 63%.…”
Section: Discussionsupporting
confidence: 91%
“…26,29,30,39 Our study observed that the respondents perceive that the intense workload, high patient expectation and substance abuse were the important contributing factors to the violence against the health care workers similar to the study conducted in Jordan by Darawad et al in 2015 while some other studies have found factors like Direct contact of HCW with highly stressed patients and families because of illness, unrestricted movements of visitors in the hospitals, overcrowding, lack of staff training in prevention and management of aggression and violence, unsatisfied treatment plan, low staffing level, prevalence of weapons among patients/relatives, communication gap, long waiting periods as some of the contributing factors towards the high prevalence of workplace violence in healthcare settings. 26,33,[35][36][37][40][41][42][43] Ever reporting of violence was observed to be very high and encouraging in the current study but more research is required to find out the prevalence of regular reporting of such incidents as the studies globally have shown that only a fraction of these matters are reported. 26,28,29,[44][45][46] The current study indicated that the approx.…”
Section: Discussionmentioning
confidence: 84%
“…The findings of our study were in coherence with many studies which indicate that nurses are exposed to high rates of workplace violence. 1,19,[26][27][28][29][30][31][32][33][34][35][36][37] These findings are a cause of concern considering the fact that workplace violence is associated with intentions to leave the profession. 22,38 The current study indicated that in majority of cases patients relatives were the perpetrators of the violence.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies (n = 13 out of 15) were conducted after 2010 in different states of India including Delhi (n = 3), [39][40][41] Manipur (n = 2), 53,54 Uttar Pradesh (n = 2), 55,56 Maharashtra (n = 1), 57 Haryana (n = 1), 58 Gujarat (n = 1), 59 and Punjab (n = 1). 60 The quality evaluation using the NHLBI tool found no studies with poor quality, three studies with fair quality, 39,51,57 and remaining studies (n = 12) with good quality. 40,41,61,62,[52][53][54][55][56][58][59][60] Most of the studies (n = 14) recruited study participants from medical institutions in urban areas whereas only one study by Pund et al recruited from multiple locations in a district where 65.85% participants were working in rural areas.…”
Section: Characteristics Of the Recruited Studiesmentioning
confidence: 99%
“…40,41,61,62,[52][53][54][55][56][58][59][60] Most of the studies (n = 14) recruited study participants from medical institutions in urban areas whereas only one study by Pund et al recruited from multiple locations in a district where 65.85% participants were working in rural areas. 57 All these studies were cross-sectional in nature and conducted using self-administered pre-tested questionnaires with different demographic and violence-related variables. While most of the studies (n = 14) reported the magnitude of violence in percentage, one study by Balamurugan reported the findings using violence score among the victims.…”
Section: Characteristics Of the Recruited Studiesmentioning
confidence: 99%